Um estudo do método simplex e sua aplicação na radioterapia - Salvador, Thaís Reigadas (2016)
This work presents an application of the Simplex Method for solving an optimal planning problem for cancer treatment by radiotherapy. The Simplex Method, proposed by George Dantzig, is a matrix procedure walks along extreme points of the feasible region in search of an optimal solution problem. The optimal planning for radiation therapy can be aided by Linear Programming, where the concern is to aplly a high enough radiation in the tumor while saving significantly healthy regions or critical organs.